Dipeptidyl Peptidase 4/Midline‐1 Axis Promotes T Lymphocyte Motility in Atherosclerosis (Adv. Sci. 9/2023). Issue 9 (24th March 2023) - Rao, Xiaoquan; Razavi, Michael; Mihai, Georgeta; Wei, Yingying; Braunstein, Zachary; Frieman, Matthew B.; Sun, Xiao Jian; Gong, Quan; Chen, Jun; Zhao, Gang; Liu, Zheng; Quon, Michael J.; et al.
Abstract : Atherosclerosis T lymphocyte infiltration in the plaque is a crucial process of atherosclerosis development. In article number 2204194, Jixin Zhong and co‐workers report a novel mechanism regulating the migration of T lymphocytes to the atherosclerotic lesions. This study not only fills a knowledge gap in our understanding of the pathogenesis of atherosclerosis, but also provides a new therapeutic target for vascular inflammation.